Augmented Reality-assisted Pictorial Storybook: Media to Enhance Discipline Character of Primary School Students - Lubis, Azmil Hasan; Wangid, Muhammad Nur (Mimbar Sekolah Dasar, 2019)
This research is intended to determine the effectiveness of Augmented Reality (AR)-assisted pictorial storybook in improving discipline character of primary school students. The population of this research was all state-run primary schools in in Sleman Regency, Special Region of Yogyakarta, Indonesia. Specifically, the samples were fourth-grade students from two primary schools, where each of them was selected to be control and experiment groups. The method used is an experimental research, while the sampling technique was cluster random sampling technique. The data collection technique was disciplinary character observation technique. Furthermore, the data were analyzed using t-test technique. The results of this research indicated that the value of sig. t-test was 0.00 (0.05). Thus, it can be concluded that AR-assisted picture storybook was considered effective in enhancing disciplinary character of primary school students. Therefore, it is recommended that the use of AR can be improved and disseminated to reach the learning objectives of primary school students, specifically in enhancing discipline character.